IDENTIFIKASI FAKTOR PENENTU HARGA KAYU BAKAU (Rhizophora sp.) DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Sribudiani, Evi (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
Tembilahan subdistrict is one of the subdistricts included in the part of Indragiri Hilir Regency. This area is known for its wetland soil with the character of clay soil. Thus,mangrove wood is one of the alternatives that are often used as raw materials for building construction in Tembilahan Sub-district such as the use of mangrove wood as a foundation and designof buildings. This research is done by employingQualitative Descriptive analysis approach. The data wereobtained from the results of in-depth interviews, observations and document studies. Further, the informant was retrieved by Snowball Sampling and Census (Saturated Sampling) technique.Thesociety in Kecamatan Tembilahan are still utilizing and marketing traditional mangrove wood. The selling price of mangrove wood offered to consumers varies considerably. The selling price of mangrove wood isinfluenced by several factors, such as production cost, bargaining communication, mangrove transport distance to the consumer location, availability of mangrove wood in nature, demand, mangrove wood size and market condition. On the other hand, the factor determines mangrove wood price in Tembilahan sub-district market is the interaction of Demand and Supply in the market. Traders of mangrove wood in Tembilahan Subdistrictare as price takers.